Relationship between protein energy malnutrition and urinary tract infection in children - Arief Wijaya Rosli; Syarifuddin Rauf; J. S. Lisal; Husein Albar; Dasril Daud (Paediatrica Indonesiana, 2008)
Background Urinary tract infections (UTI) is a common healthproblem in children. Its occurrence depends on several predis-posing factors and individual immunocompetence. Childrenwith protein energy malnutrition (PEM) have impaired immunefunction. Thus early detection and prompt treatment of associatedinfections in children with PEM are very important.Objective To determine the relationship between PEM and theoccurrence of UTI in children.Methods This cross sectional study conducted in Dr. Wahidin Sud-irohusodo Hospital and Labuang Baji General Hospital, Makassarbetween March 1, 2007 and June 30, 2007. The target populationincluded PEM patients aged 2 to 5 years. Well-nourished patientsmatched for age and sex were selected for control group.Results Out of 220 patients, 25 had UTI consisted of 12 malesand 13 females. Eighteen of them had PEM and 7 were well-nourished subjects. There was a statistical significant difference(P=0.019) in the occurrence of UTI between children with PEMand in well- nourished children. The relationship between PEMand UTI as determined by prevalence ratio value (PR) was 2.6with 95% confidence interval (CI) of 1.1 to 5.9, suggested therisk of getting UTI was 2.6 times higher in children with PEM ascompared to normal controls.Conclusions The frequency of UTI in PEM was 16.4%. Chil-dren with PEM have the risk of getting UTI 2.6 times higheras compared to well-nourished children